Carbon Footprint in Fossil Power Plants and Nuclear Energy Systems - Ida Nurfaida Nur; Nugroho Adi Sasongko; Mohammad Sidik Boedoyo (CV. AFDIFAL MAJU BERKAH, 2024)
The energy sector, including electricity, heat, and transportation, is the main contributor to GHG emissions because it handles 73.2%. Given the increasingly real threat of the climate crisis, a commitment to reduce the amountof emissions released into the environment needs to be made. One of the emission avoidance measures is an energy transition that shifts dependence on fossil energy to other, cleaner energy sources. As a less polluting technology, nuclear energy ensures a pure environment, thereby enhancing human well-being. Nuclear energy provides and develops greater efficiency and adaptability. It provides access to cheap, reliable, carbon-free energy for industrialized and developing countries. Sixty gigatons of carbon emissions avoided over the last 50 years because of nuclear energy. This form of energy distributes a lot of energy without releasing a lot of contaminants. The criterion of technical advancement must be considered when determining the relationship between the use of nuclear energy and carbon footprint because it can lead to the production of cleaner and alternative sources of energy while lowering the danger of air pollution. The findings support the hypothesis that nuclear energy use may have a negative effect on carbon footprint. These findings imply that the widespread use of nuclear energy can help minimize environmental pollution because it almost entirely eliminates carbon emissions when compared to traditional power plants that use non-renewable energy.